Broadband access in the EU: An assessment of future economic benefits - H. Gruber; J. Hätönen; P. Koutroumpis (International Telecommunications Society (ITS), 2013)
This paper evaluates the net benefits of the implementation of the broadband infrastructure deployment targets by 2020 as entailed by the Digital Agenda for Europe Initiative set forth by the European Commission. We estimate the returns from broadband infrastructure for the period 2005-2011, differentiating the impact of broadband by levels of adoption and speed while accounting for reverse causality and extensive heterogeneity. We find that in the base case scenario the overall benefits outweigh the costs by 32% for the entire European Union. We further extrapolate the returns by country under different scenarios of implementation. In most cases the benefits are substantially well above the costs. The findings lead to policy recommendations related to the role of public support for the generalized build out of broadband infrastructure.
Keywords: O33; O38; O52; 330; broadband networks; economic impact; Digital Agenda